Methods for determining the presence, character and value of wall effects in flow of polymer material - Сівецький, Володимир Іванович; Сокольський, Олександр Леонідович; Івіцький, Ігор Ігорович (Technology audit and production reserves, 2015)
One of the features of shear flow of polymer material, which is usually neglected in simplified analysis, is the presence of wall effects of various kinds, which significantly affect the accuracy of the simulation. The most significant errors arise in the calculation of the flow in the channels at the current small sections of some polymers. Wall effects can greatly affect the distribution of the main parameters of the melt across section channels and, consequently, the quality characteristics, dimensional accuracy and necessity of tuning equipment. The method of determining the presence of wall effects in the polymeric material and the nature of these effects, which allows, depending on the nature of wall effects, select the desired method for determining the magnitude of these effects. The developed methods for determining the value of wall effects allow obtaining the velocity on the wall, depending on the shear stress under different characters of wall effects – slip along the wall and the formation of low-molecular wall layer. These data can be used to set the boundary conditions of slip on the wall in the numerical simulation of non-Newtonian properties of the material.